Real-time Condition Monitoring and Asset Management of Oil- Immersed Power Transformers - Jin, Lan Maggie (Curtin University, 2024)
This research pioneers a comprehensive asset management methodology utilizing solely online dissolved gas analysis. Integrating advanced AI algorithms, the model was trained and rigorously tested on real-world data, demonstrating its efficacy in optimizing asset performance and reliability.